O Som Fora de Campo como Elemento de Construção Narrativa no Cinema Brasileiro Contemporâneo - Breno Furtado de Macedo Torquato (2020)
This dissertation presents a perspective on the use of off-screen sound as a narrative resource in contemporary Brazilian cinema through the case study of the films O Som ao Redor (2013), by Kleber Mendonça Filho; O Homem das Multidões (2013), by Cao Guimarães and Marcelo Gomes; and Chuva É Cantoria na Aldeia dos Mortos (2018), by João Salaviza and Renée Nader Messora. Based on the masking method proposed by Michel Chion, and on the theoretical concepts of Deleuze and Burch, these productions were placed in the historical panorama of sound in the Brazilian audiovisual.